2018
DOI: 10.1007/s00127-018-1566-2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of depressive symptoms among Jamaican fathers of newborns

Abstract: We interpret these findings in light of existing work on paternal depression, including the importance of social context and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
0
14
0
5
Order By: Relevance
“…Other factors associated with paternal depressive symptoms reported in this review included unexpected pregnancy, 18,19,44 older paternal age, 4 younger paternal age, 19,36 fewer biological children, 31 gender preference for a male child, 17,18 not being married, 20 length of relationship with partner less than 2 years, 29 poor sleep quality, 4 and history of infertility treatment 45 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors associated with paternal depressive symptoms reported in this review included unexpected pregnancy, 18,19,44 older paternal age, 4 younger paternal age, 19,36 fewer biological children, 31 gender preference for a male child, 17,18 not being married, 20 length of relationship with partner less than 2 years, 29 poor sleep quality, 4 and history of infertility treatment 45 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Work-related stress was reported in two studies, 2,40 both of which found a statistically significant association with paternal postpartum depression (Table 3). Lack of support from family and friends was reported as a potential risk factor for postpartum depression in six studies, [17][18][19]25,41,42 and a meta-analysis of three of these studies involving 1831 fathers resulted in a pooled OR of 2.29 (95% CI 0.93-5.67; I 2 = 88%; Figure 3). Although all six studies individually identified a statistically significant association, the random effect meta-analytic estimate of the three studies was not significant, which was suggestive of heterogeneity in the effect estimates between studies.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…Dejavniki tveganja za pojav poporodne depresije pri očetih so: prisotnost poporodne depresije pri partnerici, depresija v preteklosti, nižja stopnja izobrazbe, slabši ekonomski položaj in trenutno prestajanje travmatične izkušnje, kot so ločitev, resnejša bolezen ali izguba bližnjega sorodnika. Grey et al (2018) k dejavnikom tveganja dodajajo še brezposelnost in previsoka pričakovanja za starševstvo.…”
Section: Uvodunclassified
“…Raziskave (Kamalifard, Hasanpoor, Kheiroddin, Panahi, & Payan, 2014;Asper et al, 2018;Grey et al, 2018) so v preteklosti uporabljale številne različne vrste anketnih vprašalnikov za presejanje novih očetov na poporodno depresijo, ki niso bili specifični, zadnje raziskave (Bruno et al, 2020) pa uporabljajo Edinburško lestvico poporodne depresije.…”
Section: Uvodunclassified
“…The prevalence of paternal perinatal depression in Wuhan was higher than the global level of 5-10% (14,15). Firstly, this variation of paternal perinatal depression prevalence might be explained by the different depression tool.…”
Section: Strengths and Limitationsmentioning
confidence: 88%